2008
DOI: 10.1590/s1415-47572008000400014
|View full text |Cite
|
Sign up to set email alerts
|

Morphological patterns of the heteropycnotic chromatin and nucleolar material in meiosis and spermiogenesis of some Pentatomidae (Heteroptera)

Abstract: Pentatomidae is a family of Heteroptera which includes several agriculture pests that have had different aspects of their meiosis and spermiogenesis analyzed. In the present study we analyzed the morphological patterns of the heteropycnotic chromatin and the nucleolar material of Mormidea v-luteum, Oebalus poecilus and Oebalus ypsilongriseus. The three species presented multilobate testes, with three lobes in M. v-luteum and four in the Oebalus species. A karyotype with 2n = 14 chromosomes (12A + XY) was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Regarding cytogenetics, in Heteroptera, there is generally a close association of the chromocenter with the nucleolus in prophase I. Souza et al [9] found an unusual morphology of the nucleolar body, called mushroom, which supports the association of the chromocenter, probably the more stained portion (the cap) with the nucleolus (the stem). The species of this study showed a heteropyknotic body when stained with lacto-acetic orcein, and when silver impregnated showed two darker bodies which were probably the nucleolar bodies, and a lighter one which was probably the chromocenter.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Regarding cytogenetics, in Heteroptera, there is generally a close association of the chromocenter with the nucleolus in prophase I. Souza et al [9] found an unusual morphology of the nucleolar body, called mushroom, which supports the association of the chromocenter, probably the more stained portion (the cap) with the nucleolus (the stem). The species of this study showed a heteropyknotic body when stained with lacto-acetic orcein, and when silver impregnated showed two darker bodies which were probably the nucleolar bodies, and a lighter one which was probably the chromocenter.…”
Section: Discussionmentioning
confidence: 97%
“…The analysis of nucleolar organizer regions (NORs) during prophase has shown a close association of the chromocenter with the nucleolar body [9,10]. The chromocenter in Heteroptera is characterized by its heteropyknotic nature, where it can be composed of sex chromosomes or even by heterochromatic autosomes [9,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other species described in the literature have a reddish sheath, for example, Hyalymenus sp. and Neomegalotomus pallescens (Alydidae, Souza et al, 2009) (Souza et al, 2007a(Souza et al, , 2009, Nysius californicus (Lygaeidae) (Souza et al, 2007b), Antiteuchus tripterus, Mormidae v-luteum, Oebalus poecilus and Oebalus ypsilogriseus (Pentatomidae) (Souza et al, 2007c and Niesthrea sidae (Rhopalidae) (Souza et al, 2009), or yellow as in Zicca annulata (Souza et al, 2007a) or colourless as in Chariesterus armatus (Coreidae, Souza et al, 2007a) and Limnogonus aduncus (Gerridae, Castanhole et al, 2008). Comparison of the results presented here and the little data on this topic in the literature indicates that there is no pattern in the colour of the sheath, in terms of the family to which the species belong, because, for example, in the family Coreidae, the peritoneal sheath is reddish, yellowish or is not pigmented.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon differs from the more general process in which the disorganization of the nucleolus occurs during prophase in that, from diakinesis until the end of the meiotic division, it is not visible, suggesting that at the time it is already completely disorganized (Risueño and Medina, 1976). Nucleolar persistence, that is, the maintenance of visible nucleolar material after meiotic prophase, has been described in several Heteroptera species (Morielle-Souza and Azeredo-Oliveira, 2007;Costa et al, 2008;Souza et al, 2008). In Mormidea v-luteum, Oebalus poecilus and Oebalus ypsilongriseus (three Heteroptera species from the Pentatomidae family) the nucleolar material could be observed as a round corpuscle until the end of telophase I, and the round spermatids still exhibited a variable number of small nucleoli.…”
Section: Introductionmentioning
confidence: 98%